Analysis of traumatic ulcer healing time under the treatment of the Mauli banana (Musa acuminata) 25% stem extract gel - Puspitasari, Dewi; Apriasari, Maharani Laillyza (Universitas Padjadjaran, 2017)
ABSTRACTIntroduction: Traumatic ulcer is one of oral disorders that often occur. The prevalence is quite high, between 3-24% of population. Therapy of traumatic ulcer is symptomatic. People usually use Aloe vera extract gel. Previous research showed that the Aloe vera gel is equivalent with ethanol extract of 25% Mauli banana (Musa acuminata) stem in accelerating wound healing based on the number of macrophages and neovascular. The objective of the study is to find out the time difference of traumatic ulcer healing using 25% Musa acuminata stem extract gel compared to a gel containing Aloe vera extract. Methods: The research was post test design. Subjects were patients of Oral Medicine Installation in Gusti Hasan Aman Dental Hospital Banjarmasin with diagnosis of traumatic ulcer using completely random sampling method. Eight patients as samples were determined by the formula of Lemeshow. Results: there was no significant difference with p=0,724 (p>0,05) between healing time using Aloe vera gel and 25% Musa acuminata stem extract. Conclusion: At the concentration of 25% Musa acuminata stem extract gel concentration has the same healing time with Aloe vera gel, therefore can be recommended as a topical use for traumatic ulcer healing.Keywords: Musa acuminata stem, Healing time, Traumatic ulcer